Heraldische Funeralpanegyrik des ukrainischen Barock Am Beispiel des Stolp Cnot Syl'vestra Kossova - Erdmann, Martin (Vortraege und Abhandlungen zur Slavistik, 1999)
The presentation is based on the structure of the work in order to work out the receptive-aesthetic intention as clearly as possible. Overall, the author endeavored to present more general features of the heraldic panegyric literature in the concrete text example.